Family takaful in Bangladesh and its obstacles - Khan, I.; Rahman, N.N.A.; Nor, M.R.M. (2016)
Even though Bangladesh is globally known for her huge Muslim population, the concept of family Takaful was introduced in the country only few years back with aims, inter alia, to foster Islamic economy in the country. This study aims to explore the obstacles that hinder the success of family Takaful in Bangladesh. Semi-structural interview method was used to collect qualitative data from three different categories of stakeholders i.e. officers, Shariah board members and participants. The study revealed that the government introduced policy and regulations are the main cause due to achieve the optimum success. Business oriented policy of the Takaful companies and mismanagement in running the business have contributed to make the situation worse. Almost inactive and insufficient skill of Shariah board also play negative role. Due to enormous prospect, the research has suggested some strategies to overcome the obstacles for more successful family Takaful business in Bangladesh. It is anticipated that the findings and suggestions derived from this study will assist the policymakers in improving the situation. Researchers and policymakers from other countries can utilise these for comparative analysis triggering to global success of family Takaful.